The Interaction of Islam and Local Beliefs: A Study of Djawa Soenda’s Model of Religious Worship in the Review of Islamic Education - Khobir, Abdul; Khasanah, Nur; Susanto, Nanang Hasan; Pabbajah, Mustaqim; Adinugraha, Hendri Hermawan (Millah: Journal of Religious Studies, 2025)
This research aims to analyze the worship model of Agama Djawa Soenda (ADS) from the perspective of Islamic education. This research focuses on how spiritual and moral values in ADS can contribute to character-building in Islamic education. The research method used is qualitative, with data collection techniques through in-depth interviews and participatory observation of ADS adherents and document studies. The data were analyzed descriptively to explore the similarities and differences between ADS worship practices and Islamic education. The results show that, substantively, ADS has many similarities with Islam, especially in the aspects of divinity, environmental preservation, respect for parents, and nationalism. However, there are differences in the technical aspects of worship, where ADS is more influenced by local Javanese culture, while Islam follows standardized worship procedures based on sharia. The study concludes that the noble values of ADS, such as nature conservation and social ethics, have the potential to be integrated into Islamic education without having to sacrifice the basic principles of Sharia. This research offers a new contribution to understanding the interaction between local religion and Islamic education, as well as the importance of an inclusive approach in education that respects religious and cultural diversity in Indonesia.